REGRESSION ANALYSIS OF THE SEISMIC AND GEOPHYSICAL PARAMETERS AND ITS APPLICATION FOR SEISMICITY STUDY OF THE TRANSCARPATHIAN REGION - Homyak, M.; Malytskyy, D.; Astashkina, O.; Makhnitskyy, М.; Kravets, S.; Mykyta, A.; Grycai, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of this work is to interpret the experimental data (deformation, geoacoustic and earthquake parameters) and to establish their relation with the seismicity of the Transcarpathian region using statistical (regression) analysis. The correlation of geophysical parameters is described, namely: deformation, geoacoustic emission and seismic characteristics of magnitude and energy class.For construction of the statistical (regression) model, geoacoustic and deformation data for the period of 2014, as well as data of the seismological catalog provided by the seismicity department of the Carpathian region (Subbotin Institute of Geophysics of NAS of Ukraine) were used. The statistical model of seismicity is built to analyze various geophysical parameters and to establish their relationship with each other by means of regression analysis.This interconnection will give an opportunity to understand how seismicity influences the change of various environmental parameters of the Transcarpathian region. The deformation and geoacoustic data used in the work were obtained at the mode geophysical station (MGS) "Beregove" and the observation point "Janoshi" (Transcarpathia). The basic regression analysis formulas used to construct a linear statistical model are given. According to the seismic catalog, a graph of dependence between energy class (K) and magnitude (MD) for the period 2002–2016 was constructed, which confirmed their dependence, as well as a histogram of seismic activity for the period 2002–2016, from which it follows that the largest number of events was in 2015. The tables, on which graphs of seismicity dependence on deformation and geoacoustics, are presented. The relationship between the magnitude (MI) and the offset shift (lg DP) in depth (h) is shown. Studies were conducted for different depths: 1) up to 2 km, 2) from 2–5 km, 3)5–10 km and 4) from 10 km or more. The results showed that the greater the depth, the greater the relationship between the magnitude (MI) and the offset shift (lg DP) is. Such studies are needed to identify the effect of seismicity on the change of other environmental parameters, in particular, temperature, characteristics of earthquake foci, which will allow building an existing model of seismicity of the Transcarpathian region.
Keywords: regression analysis; seismicity of Transcarpathian region; deformation; geoacoustic emission